Prosopografía corintia (siglo V a.C.) - Fornis, César (Gerión. Revista de Historia Antigua, 2002)
The aim of this paper is to show the active presence and participation of a conspicuous oligarchic family —through the three generations represented by Adeimantos, Aristeos and Aeneas— in the Corinthian public life and foreign politics during the fifth century B.C.